Effects of Insulin Resistance on Myocardial Blood Flow and Arterial Peripheral Circulation in Patients with Polycystic Ovary Syndrome. Issue 8 (21st November 2014) - Aldrighi, José M.; Tsutsui, Jeane M.; Kowastch, Ingrid; Ribeiro, Alessandra L.; Scapinelli, Alessandro; Tamanaha, Sonia; Oliveira, Ricardo M.; Mathias, Wilson
<x xml:space="preserve">Abstract</x> Objective Polycystic ovary syndrome (PCOS) is associated with increased risk for cardiovascular disease. We sought to evaluate the effects of insulin resistance (IR) on myocardial microcirculation and peripheral artery function in patients with PCOS. Methods We studied 55 women (28 with PCOS without IR, 18 with PCOS and IR and 11 normal controls) who underwent laboratorial analysis, high‐resolution vascular ultrasound and real time myocardial contrast echocardiography (RTMCE). Intima–media thickness (IMT) and brachial artery flow‐mediated dilation (FMD) were evaluated by vascular ultrasound. The replenishment velocity (β), plateau of acoustic intensity (A) and myocardial blood flow reserve (MBFR) were determined by quantitative dipyridamole stress RTMCE. Results β reserve in group PCOS + IR was lower than control (2.34 ± 0.55 vs. 3.60 ± 0.6; P < 0.001) and than PCOS without IR (2.34 ± 0.55 vs. 3.17 ± 0.65; P < 0.001). MBFR in patients with PCOS without IR did not differ from those of control (4.59 ± 1.59 vs. 5.30 ± 1.64; P = 0.22) or from patients with PCOS + IR (4.59 ± 1.59 vs. 3.70 ± 1.47; P = 0.07). When comparing with control group, patients with PCOS + IR had lower MBFR (5.30 ± 1.64 vs. 3.70 ± 1.47; P = 0.01). No significant differences were found between control, PCOS without IR and PCOS + IR for FMD (0.18 ± 0.05, 0.15 ± 0.04 and 0.13 ± 0.07; P =NS) or IMT (0.48 ± 0.05, 0.47 ± 0.05 and 0.49 ± 0.07; P = NS). Conclusion Women with PCOS and IR had depressed β and MBFR as demonstrated by quantitative RTMCE, but no alteration in endothelial dysfunction or IMT. PCOS without IR showed isolated depression in β reserve, probably an earlier marker of myocardial flow abnormality.